The Contribution of Thoriqoh Naqsyabandiyah Kholidiyah in Increasing the Religious Spirituality of Students at the Baitul Mustaqim Punggur Islamic Boarding School, Central Lampung - Laelatul Karimah; Ehwanudin; M. Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the role of Thoriqoh Naqsyabandiyah Kholidiyah in improving the religious spirituality of students at the Baitul Mustaqim Punggur Islamic Boarding School, Central Lampung. This study was motivated by the decline in morals and weak spiritual values ​​​​among students, so that more focused and sustainable religious guidance is needed. The validity of the data is maintained through source triangulation techniques, using qualitative research methods with data collection techniques in the form of interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The subjects of the study were female students who actively participated in the amaliah Thoriqoh Naqsyabandiyah. The results showed that the concept of religious spirituality was built through the practice of heart awareness (dzikrullah), self-control (muraqabah), suluk, tawajjuh, rabithah, as well as the habit of living simply and disciplined. This process contributes to the formation of strong religious characters in students, such as sincerity, patience, humility, and responsibility. The practices of the Naqsyabandiyah Thoriqoh (Islamic teachings) play a role in fostering inner peace, enhancing religious discipline, and training students' self-control. These practices also encourage more religious behavioral changes and instill important values ​​in daily life. This study concludes that the Naqsyabandiyah Thoriqoh is an effective form of spiritual development in shaping character and strengthening the religious spirituality of students in Islamic boarding schools.